Systemically inoculated adjuvants stimulate pDC-dependent IgA response in local site - Sasaki, Eita; Asanuma, Hideki; Momose, Haruka; Furuhata, Keiko; Mizukami, Takuo; Matsumura, Takayuki; Takahashi, Yoshimasa; Hamaguchi, Isao (Mucosal immunology, 2023)
The stimulation of local immunity by vaccination is desirable for controlling virus replication in the respiratory tract. However, the local immune stimulatory effects of adjuvanted vaccines administered through the non-mucosal route are poorly understood. Here, we clarify the mechanisms by which non-mucosal inoculation of adjuvants stimulates the plasmacytoid dendritic cell (pDC)-dependent immunoglobulin (Ig)A response in the lungs. After systemic inoculation with type 1 interferon (IFN)-inducing adjuvants, type 1 IFN promotes CXCL9/10/11 release from alveolar endothelial and epithelial cells and recruits CXCR3-expressing pDCs into the lungs. Because adjuvant-activated pulmonary pDCs highly express major histocompatibility complex II, cluster of differentiation 80, and cluster of differentiation 86, transplantation of such cells into the lungs successfully enhances antigen-specific IgA production by the intranasally sensitized vaccine. In contrast, pDC accumulation in the lungs and subsequent IgA production are impaired in pDC-depleted mice and Ifnar1−/− mice. Notably, the combination of systemic inoculation with type 1 IFN-inducing adjuvants and intranasal antigen sensitization protects mice against influenza virus infection due to the pDC-dependent IgA response and type I IFN response. Our results provide insights into the novel mucosal vaccine strategies using non-mucosal inoculated adjuvants.